2002
DOI: 10.1034/j.1600-0544.2002.02198.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the expression patterns of two LIM‐homeodomain genes, Lhx6 and L3/Lhx8, in the developing palate

Abstract: Lhx6 and L3/Lhx8 functions may be partially redundant in the mesenchyme of the secondary palate, but not in the palatal epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…LHX6 Expression in Craniofacial/Tooth Epithelial and Mesenchymal Tissues and Cells-DNA microarray analyses of E16.5 and P1 excised dental epithelium and mesenchyme revealed high levels of Lhx6 transcripts in both tissues, with slightly more in the epithelial compartment. Real-time PCR confirmed Lhx6 expression in both tissues and also confirmed previous reports of Lhx6 expression in these tissues by in situ hybridization (9,11,12). LHX6 expression was also observed in the dental mesenchymal (MDPC 23) cell line and oral epithelial (LS-8) cell line.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…LHX6 Expression in Craniofacial/Tooth Epithelial and Mesenchymal Tissues and Cells-DNA microarray analyses of E16.5 and P1 excised dental epithelium and mesenchyme revealed high levels of Lhx6 transcripts in both tissues, with slightly more in the epithelial compartment. Real-time PCR confirmed Lhx6 expression in both tissues and also confirmed previous reports of Lhx6 expression in these tissues by in situ hybridization (9,11,12). LHX6 expression was also observed in the dental mesenchymal (MDPC 23) cell line and oral epithelial (LS-8) cell line.…”
Section: Discussionsupporting
confidence: 72%
“…However, Lhx6/7-deficient mice present with molar agenesis, supernumerary incisor-like teeth, cranial skeletal defects, and a cleft palate (11). This study revealed redundant activities of these two co-expressed factors in craniofacial development (9,11,12). Our Lhx6-deficient mice also do not present with severe cranial defects, but we have identified both upper and lower incisor and molar developmental defects, although these defects are subtle in nature.…”
Section: Pitx2 Regulates Lhx6 Expression and Lhx6 Acts As A Tran-mentioning
confidence: 73%
See 1 more Smart Citation
“…The expression was also detected in the rostral edge of the mandibular process, albeit with weak to moderate intensity. These expression patterns were more restricted than those of the mouse embryo (Zhang et al 2002), and those of other transcriptional factors such as Msx-1 or -2 (Brown et al 1993; data not shown). The expression area expanded gradually upwards with a peak at stage 27 HH (n=5; Fig.…”
Section: L3/lhx8 Expression In Facial Primordiamentioning
confidence: 99%
“…Lhx6 and L3/Lhx8 are expressed, with overlapping patterns, in the craniofacial regions of the developing mouse. L3/Lhx8 signal is detected in palatal mesenchyme more intensely than the Lhx6 signal (Zhang et al 2002). L3/Lhx8 gene transcript is also essential for the formation of secondary palate because its knockout mice exhibited a complete cleft palate (Zhao et al 1999(Zhao et al , 2003Mori et al 2004).…”
Section: Introductionmentioning
confidence: 99%